2021
DOI: 10.21825/digest.v8i2.17557
|View full text |Cite
|
Sign up to set email alerts
|

Allies, access and (collective) action: Young refugee women’s navigation of gendered educational constraints in Greece

Abstract: Contrary to popular media tropes of the ‘young, lone, male refugee’ arriving at Europe’s borders, Greece has in fact seen a steady flow of young refugee women arriving since 2015. While many wish to engage in post-compulsory (15+) education, in order to gain valuable skills and enjoy new freedoms, various factors make it difficult to do so. Based on eight months of ethnographic fieldwork – involving semi-structured interviews with refugee youth (aged 15-25) and other stakeholders – this paper details young ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…This was the case in Rezaian et al's (2020) study, which found that even though young refugee women were less likely to have completed schooling than their male counterparts, they were dedicated to seeking out and participating in the non-formal opportunities available while they waited in limbo. Hunt's (2021) findings echo this desire among young women in Greece to pursue a formal academic trajectory they have been denied previously in their home country, either due to conflict or cultural or family norms. Fincham (2020) found an equally and incredibly high interest in pursuing higher education among both young Syrian refugee men and women in Türkiye (as well as Jordan and Lebanon), but for different, gendered reasons.…”
Section: Individual-level Challenges and Supportssupporting
confidence: 56%
See 4 more Smart Citations
“…This was the case in Rezaian et al's (2020) study, which found that even though young refugee women were less likely to have completed schooling than their male counterparts, they were dedicated to seeking out and participating in the non-formal opportunities available while they waited in limbo. Hunt's (2021) findings echo this desire among young women in Greece to pursue a formal academic trajectory they have been denied previously in their home country, either due to conflict or cultural or family norms. Fincham (2020) found an equally and incredibly high interest in pursuing higher education among both young Syrian refugee men and women in Türkiye (as well as Jordan and Lebanon), but for different, gendered reasons.…”
Section: Individual-level Challenges and Supportssupporting
confidence: 56%
“…There, refugee women created their own non‐formal education spaces and, in doing so, reclaimed male‐dominated areas of the camp. Such navigational tactics to overcome barriers were also identified among young refugee women in Greece by Hunt (2021, p. 16):
they made efforts to fit in with and educate their peers; they requested and shaped learning offers to fit their needs; they engaged in ‘appropriate’, alternative learning opportunities which mitigated their family's protection concerns and/or better suited their situation; and they drew upon the support of advocates and allies to build strong, encouraging relationships and continue learning.
…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations